Indonesia’s Response in the South China Sea Disputes: A comparative analysis of the Soeharto and the post-Soeharto era - Derry Aplianta (JAS (Journal of ASEAN Studies), 2015)
Before it developed into a dispute among China and Southeast Asian nations, the South China Sea has been disputed long before it became what it is today. The post-World War II era brought a fresh start to a new chapter of dispute, as China, Taiwan, Vietnam, the Philippines, Malaysia, and Brunei Darussalam laid their claims one by one. This study contends that under Suharto’s iron fist rule, Indonesia’s interest to the South China Sea dispute grew from maintaining Indonesia’s territorial integrity to maintaining domestic stability. The former took shape after being threatened by China’s map which claimed a part of the former’s territorial waters, while the later grew in through establishing deeper trade cooperation with China. Despite the half-hearted normalization with China, Indonesia managed to establish a track-two forum for parties involved in the South China Sea dispute, which is later proven to be instrumental. Under President Yudhoyono, Indonesia gradually played its initial role from a passive into an active honest broker, which brought improvements to the process. This research attempts to show that constraint to Indonesia’s role in the South China Sea dispute originates from both the ideological and historical factors. Indonesia’s long-running ideological constraints set its priorities to its interest to the dispute, while its foreign policy doctrine serves as a pragmatic means to achieve its goals of interests. Indonesia’s past relationship with China also played a part in influencing Indonesia’s response which later evolved as the relations went through ups and downs. Moreover, the unclear integration process of ASEAN sets the task of the honest broker became a one-country-show for Indonesia.